Strategies for Genetic Improvement of Cattle in the North Patagonian Rangelands - Ortega, Julio Ariel (2016)
Fil: Ortega, Ariel. Universidad Nacional de Río Negro. Escuela de Medicina Veterinaria. Río Negro, Argentina.